A Comprehensive Urban Health Architecture in Smart Living Using Smart City Architecture Development Framework (SCADEF) - Najma Qurrotul Aeni; Yuli Adam Prasetyo; Iqbal Yulizar Mukti (Jurnal Sistem Informasi Bisnis, 2025)
In urban healthcare systems, rapid urbanization and population growth pose challenges, demanding creative approaches to deliver healthcare services efficiently and conveniently. With the global population projected to reach 68% urbanization by 2050 (United Nations, 2019), the need for integrated healthcare solutions is increasingly pressing. To address the gap in healthcare integration in Smart Living environments, this study develops a Smart Living Enterprise Architecture using the Smart City Architecture Development Framework (SCADEF). This study aims to integrate urban design principles into the architecture to enhance healthcare integration with other domains, promote interoperability between sectors, and citizen-centric service delivery. Using a qualitative design-focused methodology, this study leverages customer journey maps to identify healthcare interaction points and enhance user experience. The architecture is validated through stakeholder interviews and expert reviews. Through SCADEF, the proposed architecture supports smart living by integrating healthcare into the broader ecosystem, resulting in more seamless service delivery, reduced fragmentation, increased responsiveness, and improved accessibility. The findings also suggest that urban data mining can support sustainable health models and non-instant urban governance. These models can be tailored to different urban contexts, providing a holistic response to fragmented urban health services while promoting proactive and resilient public health systems.